PERCEPTIONS OF THE FACTORS THAT INFLUENCE THE LABOUR PRODUCTIVITY OF PROCUREMENT EMPLOYEES IN E-COMMERCE COMPANIES UNDER TELEWORK CONDITIONS - Ovidiu-Iulian BUNEA (Management & Marketing)
This study investigates several factors that underlie the perception of procurement employees in e-commerce companies, regarding labour productivity in the context of telework during the COVID-19 pandemic. For this, we used a representative sample of 134 companies with e-commerce activity in Romania. Thus, with the help of multiple linear regression, relevant influences were identified between the level of autonomy of the employee, called discretion-to-work, working conditions provided by the employer, employee life satisfaction and productivity perceived by them under telework conditions. Generally, we notice positive effects of telework on employees' perceptions of productivity.